1991
DOI: 10.1083/jcb.114.6.1243
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ankyrin isoforms at neuron cell bodies and nodes of Ranvier resolved using erythrocyte ankyrin-deficient mice.

Abstract: Abstract. Isoforms of ankyrin (ankyrinSR) immunologically related to erythrocyte ankyrin (ankyrrnno) are associated with distinct neuronal plasma membrane domains of functional importance, such as cell bodies and dendrites, axonal hillock and initial segments, and nodes of Ranvier. Ankyrrnno is expressed in brain, and accounts for at least one of the ankyrinR isoforms . Another ankyrin isoform of brain, ankyrinB, is encoded by a distinct gene and is immunologically distinct from ankyrins R. Mutant mice with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 40 publications
(62 reference statements)
1
71
0
Order By: Relevance
“…This specialization appears to have evolved from the tissue-specific, developmentally regulated expression of multiple protein isoforms. Ankyrin isoform diversity arises from different gene products, from differential, alternative splicing of the same gene product, from alternate polyadenylation, from the use of tissue-specific promoters, and/or the use of alternate NH 2 or COOH-termini [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Although numerous ankyrin-1 isoforms are visualized on Western blots of erythrocyte membranes [16], it is unknown if isoforms of ankyrin-1 are generated in erythroid cells by use of alternate translation initiation codons.…”
Section: Introductionmentioning
confidence: 99%
“…This specialization appears to have evolved from the tissue-specific, developmentally regulated expression of multiple protein isoforms. Ankyrin isoform diversity arises from different gene products, from differential, alternative splicing of the same gene product, from alternate polyadenylation, from the use of tissue-specific promoters, and/or the use of alternate NH 2 or COOH-termini [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Although numerous ankyrin-1 isoforms are visualized on Western blots of erythrocyte membranes [16], it is unknown if isoforms of ankyrin-1 are generated in erythroid cells by use of alternate translation initiation codons.…”
Section: Introductionmentioning
confidence: 99%
“…Resolution of the protein composition of these domains began with the discovery that both AIS and nodes of Ranvier are endowed with high local concentrations of voltage-gated sodium channels (VGSCs) (8). VGSCs copurified with membrane skeletal proteins, leading to the discovery that these channels associated directly and colocalized with the ankyrin family of membrane adaptors (9)(10)(11). The prototype ankyrin in erythrocytes couples the anion exchanger to a membrane-associated spectrin-actin network, suggesting the possibility of a similar function in stabilizing VGSC assemblies in the axon (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The immunofluorescence localization of an ankyrin isoform to these sites supports a central role for this molecule in the formation and/or maintenance of such specialized membrane domains [52]. This isoform is not recognized by antibodies raised against ankyrin, or ankyrin, and is still present at normal levels in the nb mutation [48], suggesting that this isoform represents a third member of the ankyrin gene family expressed in nervous tissue.…”
Section: Ankyrinmentioning
confidence: 91%
“…Later studies have revealed that ankyrin, is also absent from the brain of these mice resulting in a neurodegenerative disorder [47]. These experiments, along with immunofluorescent studies using an antibody against the alternatively spliced exon discussed earlier, show that ankyrin, expression is limited to the plasma membrane of cell bodies and dendrites in specific neuronal populations in the rodent nervous system [48]. Expression in neurons of the cerebellum appears to be ubiquitous and the protein is seen in a large number of neurons in both the spinal cord and metencephalon.…”
Section: Ankyrinmentioning
confidence: 95%